2023
DOI: 10.1136/oemed-2022-108713
|View full text |Cite
|
Sign up to set email alerts
|

Occupational risk of SARS-CoV-2 infection: a nationwide register-based study of the Danish workforce during the COVID-19 pandemic, 2020–2021

Abstract: ObjectiveMost earlier studies on occupational risk of COVID-19 covering the entire workforce are based on relatively rare outcomes such as hospital admission and mortality. This study examines the incidence of SARS-CoV-2 infection by occupational group based on real-time PCR (RT-PCR) tests.MethodsThe cohort includes 2.4 million Danish employees, 20–69 years of age. All data were retrieved from public registries. The incidence rate ratios (IRRs) of first-occurring positive RT-PCR test from week 8 of 2020 to wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 34 publications
0
3
0
2
Order By: Relevance
“…A limitation to tailoring covid-19 responses was the lack of person level data collection inclusive of social determinants of health including racial identity and exposure risks such as occupation and housing. Such person level data are part of routine data systems in countries (eg, Denmark, Sweden) that were able to quickly provide some of the earliest and powerful evidence of health inequalities 5152. This limitation in data, alongside critical governance issues,53 shows that Canada was not prepared to respond systematically to a pandemic shaped by health inequalities.…”
Section: Tailoring Research and Data Informed Local Responsesmentioning
confidence: 99%
“…A limitation to tailoring covid-19 responses was the lack of person level data collection inclusive of social determinants of health including racial identity and exposure risks such as occupation and housing. Such person level data are part of routine data systems in countries (eg, Denmark, Sweden) that were able to quickly provide some of the earliest and powerful evidence of health inequalities 5152. This limitation in data, alongside critical governance issues,53 shows that Canada was not prepared to respond systematically to a pandemic shaped by health inequalities.…”
Section: Tailoring Research and Data Informed Local Responsesmentioning
confidence: 99%
“…Research has shown that work in DCCs increases the risk of hospitalization due to pneumonia (14). Moreover, recent findings by Bonde et al (15) reveal that childcare workers in Denmark faced an elevated risk of contracting COVID-19 during the pandemic, like that of healthcare workers. Notably, employees in DCCs and teachers exhibit one of the highest sickness absence rates in Denmark, with an average of 13.5 sick days per year compared to approximately 8 days per year for all employees (16).…”
Section: Introductionmentioning
confidence: 99%
“…In the United Kingdom, for example, in a cohort study of residents across the country, a higher risk of infections was found in males and with a lower level of education 5 . In Denmark, a national occupational cohort allowed identifying a higher risk in healthcare occupations 6 .…”
Section: Introductionmentioning
confidence: 99%